2021
DOI: 10.18632/aging.202770
|View full text |Cite
|
Sign up to set email alerts
|

WTAP promotes myocardial ischemia/reperfusion injury by increasing endoplasmic reticulum stress via regulating m6A modification of ATF4 mRNA

Abstract: Myocardial infarction (MI) is one of the leading causes of death. Wilms' tumor 1-associating protein (WTAP), one of the components of the m 6 A methyltransferase complex, has been shown to affect gene expression via regulating mRNA modification. Although WTAP has been implicated in various diseases, its role in MI is unclear. In this study, we found that hypoxia/reoxygenation (H/R) time-dependently increased WTAP expression, which in turn promoted endoplasmic reticulum (ER) stress and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 33 publications
(34 reference statements)
1
49
0
Order By: Relevance
“…m6A is regulated by m6A methyltransferases and demethylases and controls the fate of target mRNA by affecting splicing, translation, and decay. Recently, some researches suggested that m6A modification exhibits importantly in the development of cardiac remodeling and cardiomyocyte contractile function ( Dorn et al, 2019 ; Huang et al, 2019 ; Han et al, 2021 ; Wang et al, 2021 ). For example, ablation of METTL3 weakened MI-caused myocardial fibrosis by impeding the activation of cardiac fibroblasts ( Dorn et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…m6A is regulated by m6A methyltransferases and demethylases and controls the fate of target mRNA by affecting splicing, translation, and decay. Recently, some researches suggested that m6A modification exhibits importantly in the development of cardiac remodeling and cardiomyocyte contractile function ( Dorn et al, 2019 ; Huang et al, 2019 ; Han et al, 2021 ; Wang et al, 2021 ). For example, ablation of METTL3 weakened MI-caused myocardial fibrosis by impeding the activation of cardiac fibroblasts ( Dorn et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ablation of METTL3 weakened MI-caused myocardial fibrosis by impeding the activation of cardiac fibroblasts ( Dorn et al, 2019 ). WTAP promotes MI via modulating ATF4 ( Wang et al, 2021 ). ALKBH5 mediated the modulation of heart regeneration via demethylating YTHDF1 mRNA ( Han et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the study of RNA modifications, epitranscriptomics remains in its infancy, methodological breakthroughs of the last decade have enabled identification of these modifications with such accuracy that their large-scale screening is rational [ 117 , 118 , 119 , 120 , 121 , 143 ]. Encouragingly, research findings suggest both m 6 A and A-to-I to act as contributors or even potential initiators and drivers for several cardiovascular physiological and pathological processes including cardiogenesis, angiogenesis, hypertension, hypertrophy, atherosclerosis, ischemia, ischemia-reperfusion, fibrosis, HF, congenital heart disease, stroke, aneurysms, as well as cardiac repair and regeneration [ 25 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 51 , 52 , 53 , 54 , 55 , 56 ]. Remarkably, the first indication for coronary atherosclerosis to be reflected in the m 6 A content of mRNAs and long non-coding RNAs of peripheral mononuclear cells with suggested involvement in its pathophysiology has just recently been reported [ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing or overexpression of enzymes controlling m 6 A abundance has revealed the role of m 6 A in driving immune reactivity, proliferation, apoptosis, and many intracellular processes including mRNA splicing, translation, and degradation [ 20 , 26 ], as well as miRNA biogenesis [ 27 ]. Moreover, reports from diverse fields of research [ 28 , 29 , 30 , 31 ], and in an array of cardiovascular pathologies [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], provide evidence of m 6 A as a master post-transcriptional regulator.…”
Section: Introductionmentioning
confidence: 99%